The Effect of Bionic Brake Drum Point Unit Body on Friction and Wear of Brake Pad. (November 2020) - Hu, Haiyan; Yang, Haiyang; Yang, Jiandong; Wang, Qingnian; Zhou, Ti
Abstract: In this paper, the elasticity theoretical analysis has been used to analyze the interaction between the point unit body on the bionic brake drum and the brake pad. Through the analysis, the contact stress distribution law of their interaction has been obtained, and the change in friction and wear of brake pad based on the point unit body is calculated according to the stress distribution law. Only considering the change of the surface feature regardless of other factors, the friction and wear of the point unit body on the brake pad has increased by more than 50%. Based on the research, it is indicated that the small convex point unit bodies are added on the surface of the bionic brake drum, which make the contact surface between the brake drum and the brake pad no longer the original plane contact, and the pressure and direction between the contact surfaces are different. In addition, even if the external pressure remains unchanged, the contact pressure between two surfaces will be increased, thereby increasing the friction and wear of the brake pad.